Strategies among Students of Guilan University of Medical Sciences - MAryam Niknami; Fatemeh Dehghani; Shahnaz Bouraki; Ehsan Kazem Nejad Leili; Robabeh Soleimani (Guilan University of Medical Sciences, 2014)
Abstract Introduction: Stress is an undeniable fact of human life and is known as one of most important causes of diseases therefore response to stress can have important role in adaptation. Objective: This study aims to determine coping strategies among students of Guilan University of Medical Sciences. Methods: This descriptive cross sectional study was conducted on 487 medical science students who were chosen randomly by stratified sampling method. The questionnaire consisted of two parts including social demographic and Lazarus Coping Strategies Questionnaire. Data analysis was done using descriptive statistics and chi-square. Results: Results showed that 71.9% of samples were female and 27.9% of them were male. The majority of them were studying at undergraduate level (61.4%) in nursing (25.9%). Result indicated that problem-oriented strategies are the most common coping strategy among students. Also there was a significant statistical relationship between coping strategies and with gender (p=0.03) and probation status (P=0.005). Conclusion: The main finding of study indicated that most students use problem-oriented strategy while confronting stressful situations. Given that mental health of medical science students is important because of their role in clinical settings caring for patients, planning to teach proper coping strategies is recommended.